A nurse practitioner–led telehealth protocol to improve diabetes outcomes in primary care. Issue 10 (14th October 2022) - Momin, Rashmi P.; Kobeissi, Mahrokh M.; Casarez, Rebecca L.; Khawaja, Mubarak
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: Diabetes-related complications contribute to a costly health burden in the United States. Telehealth (TH) is a tool that can increase access to care and offer ongoing support for chronic disease self-management. Local Problem: A primary care practice in Texas needed a method to manage an influx of patients with uncontrolled diabetes and improve type 2 diabetes outcomes using nurse practitioner (NP) TH appointments. Methods: Thirty patients meeting inclusion criteria participated in monthly TH check-ins and followed monthly for 3 months. Baseline and postintervention diabetes laboratory studies (hemoglobin A1c [HbA1c], estimated glomerular filtration rate, and microalbumin) were collected. Interventions: During each monthly TH visit, an NP-led diabetes TH QI protocol was implemented. The Telehealth Usability Questionnaire was administered to patients after the 3-month intervention. Results: The TH QI protocol resulted in an overall ∼1% reduction in HbA1c. Over 73% of participants experienced various reductions of HbA1c, of which 2.3% achieved a postintervention HbA1c <7%, indicating controlled diabetes. Kidney function indicated by eGFR improved by 7 ml/min/1.73 m 2 in 83% of participating patients. At the end of the 3-month intervention, 84% of participants expressed overall satisfaction with TH appointments. Conclusions: Interventions using TH to improve chronic disease may be useful in diabetes outcomes and self-management. Monthly TH visits can improve patient outcomes, reduce complications, and enhance the patient–provider relationship. Preventive self-care activities and long-term use of TH visits for self-management are implications for future studies.